2021
DOI: 10.1186/s12935-021-01988-8
|View full text |Cite
|
Sign up to set email alerts
|

LINC00261: a burgeoning long noncoding RNA related to cancer

Abstract: Long noncoding RNAs (lncRNAs), are transcripts longer than 200 nucleotides that are considered to be vital regulators of many cellular processes, particularly in tumorigenesis and cancer progression. long intergenic non-protein coding RNA 261 (LINC00261), a recently discovered lncRNA, is abnormally expressed in a variety of human malignancies, including pancreatic cancer, gastric cancer, colorectal cancer, lung cancer, hepatocellular carcinoma, breast cancer, laryngeal carcinoma, endometrial carcinoma, esophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 103 publications
(153 reference statements)
0
11
0
Order By: Relevance
“… 21 Meanwhile, the hard-done work of our peers has indicated the use of LINC00261 as a tumor inhibitor in various cancers including EC, due to its ability to modulate cellular survival, death, development, and chemoresistance as well as promoting prognostic consequences. 22 At this conjecture, we speculated if LINC00261 could serve as a benign indicator of EC, and subsequently explored the underlying interplay of LINC00261 in EC radioresistance, aiming to provide novel insights for EC amelioration.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Meanwhile, the hard-done work of our peers has indicated the use of LINC00261 as a tumor inhibitor in various cancers including EC, due to its ability to modulate cellular survival, death, development, and chemoresistance as well as promoting prognostic consequences. 22 At this conjecture, we speculated if LINC00261 could serve as a benign indicator of EC, and subsequently explored the underlying interplay of LINC00261 in EC radioresistance, aiming to provide novel insights for EC amelioration.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA LINC00261, firstly identified in hepatocellular carcinoma cells 9 years ago, is located on the 20th chromosome from site 22,560,552 to 22,578,642 ( 177 ). An increasing number of studies have indicated that LINC00261 is widely lowly expressed in a variety of cancers and acts as a tumor suppressor contributing to modulating cell proliferation, apoptosis, invasiveness, migration, chemoresistance, angiogenesis, and tumorigenesis via multiple molecular mechanisms ( 177 ). LINC00261 also plays vital roles in suppression of PC progression by acting as a ceRNA.…”
Section: Linc00261/mir-222-3p/hipk2mentioning
confidence: 99%
“…Human lncRNA DEANR1/linc00261 is involved in many cellular processes, including ones crucial for cancer development [ 13 , 14 , 15 , 16 ]. Linc00261 expression is downregulated in several cancer types, such as HCC, pancreatic, gastric, colorectal, lung and breast cancers [ 17 ]. Linc00261 as a tumor suppressor inhibits the growth of cancer cells primarily by inhibiting cell proliferation and stimulating cell apoptosis [ 18 ], and also reduces the invasiveness of cancer cells by inhibiting the epithelial–mesenchymal transition (EMT) [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, linc00261 can act as ceRNAs, which sponge miRNA and affect the mRNA levels of target genes. Many target genes of linc00261 participate in multiple signaling pathways, such as the Wnt/β-catenin signaling pathway, p38 MAPK signaling pathway and Notch signaling pathway [ 17 ]. Murine lncRNA Falcor/LL35 (NCBI—9030622O22Rik) has been defined as a possible functional analog of human lncRNA DEANR1/linc00261, which is predominantly expressed in murine lungs and liver, intestine and pancreas [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%